Trichoscopy findings in dissecting cellulitis - Daniel Fernandes Melo; Erica Bertolace Slaibi; Thais Marques Feitosa Mendes Siqueira; Violeta Duarte Tortelly (Sociedade Brasileira de Dermatologia, 2019)
Abstract Dissecting cellulitis is an inflammatory, chronic, and recurrent disease of the hair follicles that mainly affects young Afro-descendent men. Trichoscopy is a method of great diagnostic value for disorders of the scalp. Clinical and trichoscopic findings of dissecting cellulitis are heterogeneous and may present features common to non-cicatricial and scarring alopecia. This article presents the trichoscopic findings of dissecting cellulitis that help in the diagnosis and consequent institution of the appropriate therapy and better prognosis of the disease.